Status Gizi dan Kemampuan Motorik Anak dengan Cerebral Palsy - Ika Rosdiana; Lia Nor Hidayah; Wiwik Lestari; Iktamala Silmia (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Cerebral palsy will cause motor damage which can be observed through gross motor skills. Neurological disorders in cerebral palsy can cause a lack of nutritional intake so that the nutritional status of children can be disrupted. This study aims to analyze the nutritional status of children with cerebral palsy with motor skills at YPAC Semarang. The subjects of this study were 24 children with cerebral palsy who regularly visited YPAC Semarang to undergo therapy, who were selected by total sampling technique. Nutritional status and motor skills were assessed using the Gillette Functional Assessment Questionnare (FAQ), the Level of Sitting Scale (LSS), and the Gross Motor Function Measure Score dimension A. A sample of children with cerebral palsy had a normal nutritional status of 54.2%. The motor skills of children with cerebral palsy: 33.3% were unable to walk, the score on the LSS level of sitting scale: 41.7% were able to sit without a backrest, while for GMFM: 62.5% were good back muscle strength. It was concluded that the nutritional status of children with cerebral palsy was generally normal, sitting ability and trunk strength were good, but most were unable to walk.Keywords: nutritional status; cerebral palsy; gross motor function measure; gillette functional assessment questionnare; level of sitting scaleABSTRAK Cerebral palsy akan menimbulkan kerusakan motorik yang dapat diamati melalui kemampuan motorik kasar. Gangguan  neurologis pada cerebral palsy dapat menyebabkan kurangnya asupan gizi sehingga status gizi anak dapat terganggu. Penelitian ini bertujuan untuk menganalisis status gizi anak dengan cerebral palsy dengan kemampuan motorik di YPAC Semarang. Subyek penelitian ini 24 anak dengan cerebral palsy yang rutin berkunjung ke YPAC Semarang untuk menjalani terapi, yang dipilih dengan teknik total sampling. Status gizi dan kemampuan motorik dinilai menggunakan Gillette Functional Assessment Questionnare (FAQ), Level of Sitting Scale (LSS), serta Gross Motor Function Measure Score dimensi A. Sampel anak dengan cerebral palsy memiliki status gizi normal sejumlah 54,2%. Kemampuan motorik anak dengan cerebra palsy adalah: 33,3% tidak mampu berjalan, skor level of sitting scale LSS adalah: 41,7% mampu duduk tanpa sandaran, sedangkan untuk GMFM adalah: 62,5% kekuatan otot punggung baik. Disimpulkan bahwa status gizi anak dengan cerebral palsy secara umum normal, kemampuan duduk dan kekuatan trunkus baik, tetapi sebagian besar tidak mampu berjalan.Kata kunci: status gizi; cerebral palsy; gross motor function measure; gillette functional assessment questionnare; level of sitting scale